Productivity Improvement through Line Balancing Measurement in the Loom Section Using the Ranked Positional Weight (RPW) Method: Peningkatan Produktivitas Melalui Pengukuran Line Balancing Pada Section Loom Menggunakan Metode Ranked Positional Weight (RPW) - Fauzi, Abiyan Falih; Z.S, Joumil Aidil Saifuddin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The textile industry’s productivity hinges significantly on the efficiency of its production lines. Specific Background: At PT XYZ, the section loom area has persistently failed to meet monthly production targets, achieving less than 80% output. Knowledge Gap: Existing work distribution methods lack optimization, resulting in unbalanced workloads and excessive idle time. Aim: This study aims to enhance productivity through line balancing using the Ranked Positional Weight (RPW) method.Results: Initial conditions with three workstations yielded a line efficiency of 58.92%, a balance delay of 41.08%, and 422.48 minutes of idle time. Reconfiguring the system into four workstations using the RPW method increased line efficiency to 72.12%, reduced balance delay to 27.88%, and decreased idle time to 310.34 minutes. Novelty: The application of RPW in this specific section loom context provides a quantifiable strategy for balancing workloads and improving flow. Implications: These findings confirm the RPW method as an effective tool for optimizing production lines, offering a replicable solution for similar industrial settings to boost overall productivity. Highlights: Highlights the use of RPW to solve production inefficiency. Demonstrates measurable gains in efficiency and idle time reduction. Offers a replicable model for workload balancing in manufacturing. Keywords: Line Balancing, Ranked Positional Weight, Productivity Improvement, Textile Industry, Workload Optimization